PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH, PARTISIPASI PENYUSUNAN ANGGARAN PADA KINERJA INDIVIDU DENGAN PEMODERASI MOTIVASI KERJA - Adhitama, Putu Indra; Gayatri, . (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
Individual performance is the extent of work by individuals in the organization are used as the basis of an assessment the organization. The purpose of this study to determine effect of internal control system of government, budget participation on the performance of individuals and influence of work motivation in moderating the internal control system of government relations and budgeting participation in the performance of individuals in the Bangli regional work units regency. This study was conducted on 26 SKPD Bangli using a questionnaire and samples used 78 by using purposive sampling method. The analysis technique used is multiple linear regression analysis and moderated regression analysis. The government's system of internal control and budgeting participation positive effect on individual performance. Work motivation cannot moderate the influence of the internal control system of government on individual performance, but motivation to work strengthen the influence of budget participation on the performance of individuals.
Keywords: Internal Control Systems of Government, Budget Participation, Work Motivation, Individual Performance